Acute‐phase response following one‐stage full‐mouth versus quadrant non‐surgical periodontal treatment in subjects with comorbid type 2 diabetes: A randomized clinical trial - Graziani, Filippo; Gennai, Stefano; Marruganti, Crystal; Peric, Marina; Ghiadoni, Lorenzo; Marhl, Urska; Petrini, Morena (Journal of clinical periodontology, 2023)
Aim To compare the level of inflammatory markers and endothelial function 24 h (Day 1) and 90 days (Day 90) after conventional quadrant‐wise scaling and root planing (Q‐SRP) versus one‐stage full‐mouth SRP (FM‐SRP) in patients affected by type 2 diabetes mellitus (T2DM). Materials and Methods Patients affected by periodontitis and T2DM were randomly allocated to receive FM‐SRP or Q‐SRP and followed up at Day 1 and Day 90. Serum samples, vital signs, and flow‐mediated dilation (FMD) parameters were collected at baseline, Day 1, and Day 90. Periodontal variables were collected at baseline and Day 90. The primary outcome was the C‐reactive protein (CRP) concentration at Day 1 after periodontal treatment. Student's t‐test for independent samples was used for between‐group comparisons (Mann–Whitney U test for non‐normal data), while analysis of variance with post hoc Tukey tests (Kruskal–Wallis and Dunn tests for non‐normal data) were used for intra‐group comparisons. Results Forty subjects were included in the study. FM‐SRP produced a significant increase in CRP and a significant reduction in FMD at Day 1 compared to Q‐SRP (p < .05). The absolute change in HbA1c (mmol/mol) from baseline to Day 90 was significantly improved in the Q‐SRP (ΔHbA1c = −1.59 [SD = 1.20]) compared to the FM‐SRP group (ΔHbA1c = −0.8 [SD = 0.95]) (p = .04). Conclusions FM‐SRP triggers a robust acute‐phase response at 24 h after treatment compared to Q‐SRP. Such systemic acute perturbations may offset the beneficial systemic effects of periodontal treatment in terms of HbA1c reduction and improvement in endothelial function in T2DM subjects.